How bad are weather disasters for banks? - Kristian Blickle; Sarah N. Hamerling; Donald P. Morgan (Federal Reserve Bank of New York, 2021)
Not very. We find that weather disasters over the last quarter century had insignificant or small effects on U.S. banks' performance. This stability seems endogenous rather than a mere reflection of federal aid. Disasters increase loan demand, which offsets losses and actually boosts profits at larger banks. Local banks tend to avoid mortgage lending where floods are more common than official flood maps would predict, suggesting that local knowledge may also mitigate disaster impacts.
Keywords: G21; H84; 330; hurricanes; wildfires; floods; climate change; weather disasters; FEMA; banks; financial stability; local knowledge